KEPEMIMPINAN PERUBAHAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Anna Ma'ratuz Zahro; Ahmad Yusuf Sobri; Ahmad Nurabadi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: The purpose of this research to know about (1) the role of headmaster as a leadership of change, (2) the principal's strategy as a leadership of change, (3) innovation principal as a leadership of change, (4) factors supporting of change, and (5) inhibiting factors of change. This research uses a qualitative approach with case study design. Presearch location at SMA Nasional Malang. Data collection techniques with interviews, observation, and documentation. The results of this research (1) the role of headmaster as a leadership of change, the first role as visionary, responsible, locomotive, motivator, and partner work, (2) the strategy used by the principal is by improving the management of students and the management of teaching and education personnel, fostering a school culture, supervising learning, and preparing outputs thoroughly, (3) innovations made by the principal of gopek management and athlete classes, (4) the factors that support the change come from the internal school such as the principal's leadership, the support of the foundation and the means of infrastructure, from the external needs of the community for education and competition between schools, and (5) the inhibiting factors of change come from the difficult teacher's mindset, teacher competence, and poor school image in society. Keywords: changes leadership, education quality improvment Abstrak: Penelitian ini bertujuan untuk mengetahui (1) peran kepala sekolah sebagai pemimpin perubahan, (2) strategi kepala sekolah sebagai pemimpin perubahan, (3) inovasi kepala sekolah sebagai pemimpin perubahan, (4) faktor pendukung perubahan, dan (5) faktor penghambat perubahan. Penelitian ini menggunakan pendekatan kualitatif, dengan rancangan penelitian studi kasus. Lokasi penelitian ini di SMA Nasional Malang. Teknik pengumpulan data melalui wawancara secara mendalam, observasi lapangan serta dokumentasi. Hasil dari penelitian ini (1) peran kepala sekolah sebagai pemimpin perubahan yaitu pertama berperan sebagai pemimpin yang visioner, penanggung jawab, lokomotif, motivator, dan patner kerja, (2) strategi yang digunakan kepala sekolah yaitu dengan memperbaiki manajemen peserta didik dan manajemen tenaga pendidik dan kependidikan, menumbuhkan budaya sekolah, melakukan supervisi pembelajaran, dan mempersiapkan output secara matang, (3) inovasi yang dibuat oleh kepala sekolah yaitu program manajemen gopek dan kelas atlet, (4) faktor pendukung perubahan berasal dari internal sekolah seperti kepemimpinan kepala sekolah, dukungan yayasan dan sarana prasarana, dari eksternal yaitu kebutuhan masyarakat akan pendidikan dan persaingan antar sekolah, (5) faktor penghambat perubahan berasal dari mindset guru sulit diubah, kompetensi guru, dan image sekolah kurang baik di masyarakat. Kata kunci: kepemimpinan perubahan, mutu pendidikan